LPS Induces Active HMGB1 Release From Hepatocytes Into Exosomes Through the Coordinated Activities of TLR4 and Caspase-11/GSDMD Signaling - Li, Wenbo; Deng, Meihong; Loughran, Patricia A.; Yang, Muqing; Lin, Minjie; Yang, Chenxuan; Gao, Wentao; Jin, Shuqing; Li, Shilai; Cai, Jingjing; Lu, Ben; Billiar, Timothy R.; et al. (Frontiers in Immunology, 2020)
High mobility group box-1 (HMGB1), a ubiquitous nuclear protein, acts as a late mediator of lethality when released extracellularly during sepsis. The major source of circulating HMGB1 in sepsis is hepatocytes. However, the mechanism of HMGB1 release of hepatocytes during sepsis is not very clear. We have previously shown that bacterial endotoxin (LPS) sensing pathways, including TLR4 and caspase-11 regulate hepatocyte HMGB1 release in response to LPS. Here, we report the novel function of caspase-11 and GSDMD in LPS-induced active HMGB1 released from hepatocytes. HMGB1 release during endotoxemia was caspase-11/GSDMD dependent via an active way in vivo and in vitro. Caspase-11/GSDMD was responsible for HMGB1 translocation from nucleus to the cytoplasm via calcium changing induced phosphorylation of camkkβ during endotoxemia. Cleaved GSDMD accumulated on the endoplasmic reticulum, suggested this may lead to calcium leak and intracellular calcium increase. Furthermore, we investigated that exosome was an important pathway for HMGB1 release from hepatocytes, this process was dependent on TLR4, independent on caspase-11 and GSDMD in vivo and in vitro. These findings provide a novel mechanism that TLR4 signaling results in an increase in caspase-11 expression, as well as increased exosome release, while caspase-11/GSDMD activation/cleavage leads to accumulation of HMGB1 in the cytoplasm through a process associated with release of calcium from the endoplasmic reticulum and camkkβ activation.